Verbal and visual metaphors of an unfolding crisis: Emerging styles of representation in British and Italian front page news at the onset of the Covid-19 pandemic - Antonella Luporini; Claudia Roberta Combei; Ludovica Pannitto (Dive-In)
This study examines verbal and visual metaphors representing coronavirus-related issues in news discourse at the onset of the Covid-19 pandemic. Although Covid-19 metaphors have been widely investigated both during and after the health crisis, few studies have focused on the early stages of the pandemic and on non-verbal modes of communication. To address this gap, we analyse a set of front pages from British and Italian broadsheet newspapers published between February 24 and March 1, 2020, drawing on Conceptual Metaphor Theory and multimodal metaphor studies. We first outline the annotation scheme and procedure used for this study. Through qualitative analysis, we then identify a set of visual and verbal metaphors that conceptualise the coronavirus and related issues as target concepts, classifying them by source concept and examining the interaction between verbal and visual elements. This leads us to identify some emerging styles of representation, which, we argue, would also impact public discourse in the following stages of the pandemic.